Productos crediticios y su incidencia en el nivel socioeconómico de los clientes de la cooperativa de ahorro y crédito Chone limitada, del cantón Chone, periodo 2013-2014, plan de disminución de riesgos. - Basurto Santana, Glenda Dolores (2015)
This research was carried in the matrix of the credit saving cooperative Chone Limited, located in the Pichincha and Ulpiano Paez corner streets of the city of Chone, Manabí Province, has branches in the cantons of San Vicente, Flavio Alfaro and Pichincha. This study had objective to evaluate the credit products offered by the financial institution and its impact on the socioeconomic status of the partners in which it was determined the credit collocation increases during the period 2013 – 2014 at 2,74%, the credit products have helped the quality of life of society to that many people can remodel their homes, educate their children and invest in new commercial and agricultural projects; however 0.2% of the partners could not do their payments required because they don´t control their finances, deviated from the purpose of the credit, investment with low or no profitability caused by bad weather, lack of moral culture, use the credit to third person, difficulty guarantors who in many cases have to assume these debts in the credit saving Cooperative Chone Limited; It has used concepts of credit products, socioeconomic status, consumer credit, housing loans, microcredit. The methodology used was non experimental, it made surveys to 394 partner of the organization for which the equation Hernandez (2006) it was applied an interview was conducted at the boss of Credit. Sources were consulted in books, theses, laws and internet. The legal basis of this research was supported by: the Constitution of Ecuador, law Superintendence of Popular and Solidarity Economy. As a solution to the problems presented is elaborate the action to reduce risks of microcredit for the credit saving cooperative Chone Limited, its application is to reduce the level of bad debts, than their partners can manage correct the credit, with the goal supporting the economic development and institutional for which was required a budget of $ 8,604.75.